Single-Target Regulators Constitute the Minority Group of Transcription Factors in Escherichia coli K-12 - Shimada, Tomohiro; Ogasawara, Hiroshi; Kobayashi, Ikki; Kobayashi, Naoki; Ishihama, Akira (Frontiers in Microbiology, 2021)
The identification of regulatory targets of all transcription factors (TFs) is critical for understanding the entire network of genome regulation. A total of approximately 300 TFs exist in the model prokaryote Escherichia coli K-12, but the identification of whole sets of their direct targets is impossible with use of in vivo approaches. For this end, the most direct and quick approach is to identify the TF-binding sites in vitro on the genome. We then developed and utilized the gSELEX screening system in vitro for identification of more than 150 E. coli TF-binding sites along the E. coli genome. Based on the number of predicted regulatory targets, we classified E. coli K-12 TFs into four groups, altogether forming a hierarchy ranging from a single-target TF (ST-TF) to local TFs, global TFs, and nucleoid-associated TFs controlling as many as 1,000 targets. Using the collection of purified TFs and a library of genome DNA segments from a single and the same E. coli K-12, we identified here a total of 11 novel ST-TFs, CsqR, CusR, HprR, NorR, PepA, PutA, QseA, RspR, UvrY, ZraR and YqhC. The regulation of single-target promoters was analyzed in details for the hitherto uncharacterized QseA and RspR. In most cases, the ST-TF gene and its regulatory target genes are adjacently located on the E. coli K-12 genome, implying their simultaneous transfer in the course of genome evolution. The newly identified 11 ST-TFs and the total of 13 hitherto identified altogether constitute the minority group of TFs in E. coli K-12.